VISUALISASI MONOGRAFI DALAM BENTUK INFOGRAFIS DI KELURAHAN BANJAR SARI KECAMATAN METRO UTARA - Oktalia; Muharni, Sita (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2024)
The kelurahan monograph is a document containing essential data about a region, such as demographics, education, health, and economy. However, presenting data in text and tables is often difficult for the general public and policymakers to understand. This study aims to visualize the monograph data of Banjar Sari Subdistrict, Metro Utara District, in the form of informative and engaging infographics to enhance data comprehension and utilization. The research employs the Visual Data Mining (VDM) approach, which includes data collection, processing, analysis, and visualization using Tableau software. The results indicate that the generated infographics improve public understanding of their regional conditions, encourage active participation, and support data-driven decision-making. Evaluations show that infographics are easier to understand than conventional monograph documents and more effective in conveying information. This study contributes to presenting monograph data visually, making it more accessible for various stakeholders in planning better and data-driven regional development.